A Short Review of Customer Satisfaction on Mobile Banking Service Quality of Islamic Banks - Vahrul Rozie; Anna Sardiana; Puspita Puspita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2023)
Customer satisfaction is important for services company. The study aims to look out issues that need to be concern of Islamic bank as implications related to the quality of mobile banking services which can increase customer satisfaction of Islamic banks. This article reviews some previous study of customer satisfaction on mobile banking service quality of Islamic Bank. As a result, Islamic banks need to make improvements in online information system quality, where Islamic banks must be able to provide the quality of information presented in their mobile banking applications, form and manage qualified human resources, who understand in the fields of Islamic economics and banking as well as information technology and use sophisticated IT systems in their mobile banking products to compete with conventional banks.